Impact of Covid-19 in pregnancy on mother’s psychological status and infant’s neurobehavioral development: a longitudinal cohort study in China - Wang, Yuanyuan; Chen, Lian; Wu, Tianchen; Shi, Huifeng; Li, Qin; Jiang, Hai; Zheng, Danni; Wang, Xiaoli; Wei, Yuan; Zhao, Yangyu; Qiao, Jie (BMC medicine, 2020)
Evidence concerning the long-term impact of Covid-19 in pregnancy on mother's psychological disorder and infant's developmental delay is unknown. This study is a longitudinal single-arm cohort study conducted in China between May 1 and July 31, 2020. Seventy-two pregnant patients with Covid-19 participated in follow-up surveys until 3 months after giving birth (57 cases) or having abortion (15 cases). We collected data from medical records regarding Covid-19, delivery or abortion, testing results of maternal and neonatal specimens, and questionnaires of quarantine, mother-baby separation, feeding, and measuring of mothers' mental disorders and infants' neurobehavioral disorders. All cases infected in the first trimester and 1/3 of cases infected in the second trimester had an abortion to terminate the pregnancy. 22.2% of pregnant patients were suffering from post-traumatic stress disorder or depression at 3 months after delivery or induced abortion. Among 57 live births, only one neonate was positive of nucleic acid testing for throat swab, but negative in repeated tests subsequently. The median duration of mother-baby separation was 35 days (interquartile range 16 to 52 days). After the termination of maternal quarantine, 49.1% of mothers chose to prolong the mother-baby separation (median 8 days; IQR 5 to 23 days). The breastfeeding rate was 8.8% at 1 week after birth, 19.3% at the age of 1 month, and 36.8% at the age of 3 months, respectively. The proportion of "monitoring" and "risk" in the social-emotional developmental domain at the age of 3 months was 22.7% and 63.6%, respectively. After the adjustment of preterm, neonatal sex, admitted to NICU, and the mother's Covid-19 condition, the negative associations were significantly identified (p < 0.05) between mother-baby separation days and three developmental domains: communication, gross motor, and personal-social. There is no definite evidence on vertical transmission of SARS-CoV-2. In addition to control infection risk, researchers and healthcare providers should pay more attention to maternal mental health and infant's feeding, closeness with parents, and early development.